Production and purification of protein nanocages displaying binding domains - Lam, Ngo Cheung (2017)
Protein nanocages are naturally assembled structures composed of protein subunits which can be individually modified to give a multifunctional nanoplatform. Ferritin and E2 core domain are two examples of protein nanocages that can be engineered at the inner surface, external surface and interface between subunits for enhanced functionality. Here, we are interested in displaying two types of binding domains on a mutated form of Archaeoglobus fulgidus ferritin (AfFtn-AA) and Geobacillus stearothemophilus E2: cellulose-binding domain (CBD) and lipid-binding domain (LBD). A CBD from the cellulosome complex of Clostridium thermocellum and three LBDs from mammalian proteins Epsin 1, Endophilin A1 and MARCKS were identified. Seven gene fusions were designed and constructed, of which four were expressed in E. coli as soluble recombinant proteins. Purification using heat treatment, hydrophobic interaction chromatography and ion exchange chromatography were attempted. MARCKS/AfFtnAA, when tagged with six histidine residues, was the only protein found to be significantly purified using affinity chromatography and a final polishing step of size exclusion chromatography.